To Determine Frequency of Anxiety and Depression in Temporo-mandibular Joint Disorders - Ahmad Shafique, Ehsan Ul Haq, Umer Hussain, Wajiha Abbas, Sundus Iftikhar, Mujtaba Nadeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Temporomandibular disorder (TMD) is a general term that refers to disorders associated with the temporomandibular joint (TMJ) and the masticatory muscles. Due to the complexity of the masticatory system, TMD symptoms may be caused by different physiological and/or psychosocial factors, such as malocclusion and occlusal interferences, alterations in the masticatory muscles, direct trauma to the jaw or TMJ, micro trauma caused by continuous parafunctional habits Aim: To determine frequency of anxiety and depression in temporomandibular joint disorders. Methods: Cross sectional study design was conducted in the Department of Oral and Maxillofacial surgery, Mayo Hospital Lahore for a period 6 months. a total 365 cases fulfilling inclusion criteria was enrolled in study from Oral and Maxillofacial surgery Mayo Hospital Lahore. Informed written consent was taken from patients and then their data according to variables in proforma was recorded. Anxiety and depression was measured by researcher himself according to operational definition. Results: The mean age of cases was 28.95 ± 6.71 years with minimum and maximum age of 18 and 40 years. In this study there were 185(50.68%) male and 180(49.32%) female cases. The mean Hospital Anxiety and Depression (HAD) score was 12.15±11.75 with minimum and maximum score as 0 and 42. Anxiety and depression was seen in 180(49.32%) of the cases while 185(50.68%) of the cases did not has anxiety and depression. Conclusion Through the findings of this study it is found that the frequency of Anxiety and depression is very much high. So we should formulate proper treatment strategy with the help of psychiatry department to cope this issue. No doubt it will help to improve their prognosis and better quality of life. Keywords: Physical therapy specialty, Electromyography, Facial pain, Temporomandibular joint, Anxiety, Depression